Notae epigraphicae, palaeographicae, chronologicae, historiographicae (…) u radovima M. Barade - Matijević-Sokol, Mirjana (2011)
U radu se autorica osvrće na više priloga u kojima je M. Barada kao obrazovani paleograf i diplomatičar analizirao važna povijesna vrela s aspekta paleografije, diplomatike i kronologije. Radi se o diplomatičkim, epigrafskim i narativnim spomenicima iz hrvatskoga ranog srednjeg vijeka. U ovim je člancima Barada pokušao ispraviti ili na drukčiji način propitivati čitanja, datiranja i tumačenja podataka zabilježenih u ispravama, natpisima i djelima pisaca.
In this article the author discusses several smaller pieces in which Miho Barada, an expert in palaeography and diplomatics, analyzed an array of important historical sources: of diplomatic as well as epigraphic and narrative nature. In these essays, Barada attempted to correct or find a new way of reading, dating and explaining information obtained in public documents, epigraphs and literary writings. Tabella plumbea Traguriensis, the charters of Dukes Trpimir and Muncimir, Zvonimir’s oath, Koloman’s charter, Vekenega’s epigraph, the epitaph of Queen Jelena and Thomas the Archdeacon’s Historia Salonitana, were all subjected to Barada’s close examination. Finally, the analysis of these essays may lead to a conclusion that Barada was a truly excellent and impeccably educated medieval scholar, who based his conclusions and results upon the great wealth of specialized knowledge: of palaeography, diplomatics and related disciplines. While we may disagree with some of his conclusions and opinions and while academic historiography has moved on since Barada’s times, his research methods still provide an exemplary model to students of history.
Projekt MZOS
Projekt MZOS
HRV